Damage Parameter Variations of Breakwater along with a Floating Wave Barrier and a Submerged Obstacle - Naseri, Alireza; Vafaeipour Sorkhabi, Ramin; Alami, Mohammad Taghi; Mojtahedi, Alireza (International Journal of Sustainable Construction Engineering and Technology, 2022)
Damage to rubble mound breakwaters (RMBs), both general and partial, causes instability and inconstancy of the structure against waves. This study aimed to investigate the effect of a submerged obstacle on the stability and damage reduction of RMBs as an innovative method and determine the optimal distance of the obstacle from the breakwater and the floating wave barrier based on the damage parameter. The waves affecting the breakwater were assumed to be random using a JONSWAP spectrum. The aggregates’ movement and the RMB’s exact deformation were recorded using close-range photogrammetric imaging, and the eroded area and the damage parameters were obtained at equal distances in eight cross-sections. According to the results of the tests, by analyzing the effect of the number of waves hitting the breakwater, 3000 waves were considered to bring the structure to a stable state. The results showed that increasing the relative wave height from 0.36 to 0.48 and from 0.48 to 0.6 increased the damage parameters to 39.12% and 44.44%, respectively, and increasing the relative wave period from 0.6 to 0.8 and 0.8 to 1 increased the damage parameters to 22.94% and 28.26%, respectively. Moreover, using a seaward obstacle at 0, 5, 10, 15, and 20 cm distances decreased the damage parameter. The greatest effect, a reduction of 39.15% in the damage parameter, was observed at a distance of 5 cm from the RMB. This number was reduced to 0.735 when a floating wave barrier was used without a submerged obstacle (i.e., 34.14%). Using an obstacle at 5 cm in conjunction with a wave barrier reduced the damage parameter by 54.03% and demonstrated the best function among different models. Hence, this model is proposed based on the experiments carried out in this study.